2015
DOI: 10.32945/atr37110.2015
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics and Nutrient Status of Two Degraded Upland Soils in Samar, Philippines

Abstract: The study evaluated the morpho-physical, chemical, and biological characteristics as well as the nutrient status of two degraded upland soils located in Sta. Rita, Western Samar and in Salcedo, Eastern Samar. Soil profiles were examined and soil erosion was determined. Composite soil and plant tissue samples were collected from different vegetation cover or crops planted by the farmers. All laboratory analyses were done following standard procedures. Results indicate that: 1) the Sta. Rita soil which is relati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 10 publications
3
10
0
Order By: Relevance
“…In terms of color development, SP1 and SP3 had colors ranging from brown to light yellowish-brown in the surface and yellowish-brown in the subsurface horizon. Similarly, it was previously observed that the color of the degraded soils in the area was dark yellowish-brown in the surface and light yellowishbrown in the subsurface (Asio et al, 2015). SP2 had colors ranging from dark yellowish-brown to light gray indicating a poorly drained soil that resulted in a reduced form of iron (Fe) oxides linked to the absence of oxygen.…”
Section: Morphological Characteristicssupporting
confidence: 56%
See 3 more Smart Citations
“…In terms of color development, SP1 and SP3 had colors ranging from brown to light yellowish-brown in the surface and yellowish-brown in the subsurface horizon. Similarly, it was previously observed that the color of the degraded soils in the area was dark yellowish-brown in the surface and light yellowishbrown in the subsurface (Asio et al, 2015). SP2 had colors ranging from dark yellowish-brown to light gray indicating a poorly drained soil that resulted in a reduced form of iron (Fe) oxides linked to the absence of oxygen.…”
Section: Morphological Characteristicssupporting
confidence: 56%
“…Similarly, in the study of Asio et al (2014), it was reported that the dominant vegetation of the degraded uplands of Inopacan, Leyte consisted of the same plants, including Andropogon aciculatus ('Amorseco') and Calopogonium muconoides ('Malabatong'). All of the plants mentioned can be considered as indicators of degraded soil (Asio, 2007;Asio et al, 2014).…”
Section: Site Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations
“…It is directly related to the porosity and indirectly related to the bulk density. Furthermore, it is mainly influenced by the soil texture as it takes the pore volume to be filled and hold a certain water volume [26]. The water holding capacity of the surface soils in Mt.…”
Section: Water Holding Capacitymentioning
confidence: 99%